Hubungan antara Fear Of Missing Out (Fomo) dengan Perilaku Konsumtif Mahasiswa Prodi Bimbingan Konseling Fakultas Keguruan dan Ilmu Pendidikan Universitas Nusa Cendana - Jangkar, Veronika Yuliani; Nalle, Andriani Paulin; Korohama, Katharina Edeltrudis Perada (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
The phenomenon of consumerist behavior among students is increasingly becoming a major concern, especially with the influence of the Fear Of Missing Out (FOMO) phenomenon. FOMO can drive individuals to engage in consumerist behavior, namely buying goods or services that are not needed just to avoid the feeling of missing out on experiences or information that is considered important. This study aims to examine the prevalence of Fear of Missing Out (FOMO) and consumptive behavior among Guidance and Counseling students at the Faculty of Teacher Training and Education, Nusa Cendana University, and to determine the relationship between FOMO and consumptive behavior. This research employs a quantitative approach with a descriptive correlational study design. The research was conducted on students of the Guidance and Counseling Study Program at the Faculty of Teacher and Education (FKIP) at Nusa Cendana University, with a population of 245 students and a sample of 116. The data collection technique uses questionnaires with the likert scale. The data analysis techniques employed were descriptive analysis and correlation analysis using the IBM SPSS Statistics 25 software. The findings revealed that 55% of the students exhibited moderate levels of Fear Of Missing Out (FOMO), while 53% exhibited moderate levels of consumptive behavior. The Pearson product-moment correlation analysis indicated a positive correlation between FOMO and consumptive behavior, with an rxy value of 0.597. Furthermore, the correlation significance test demonstrated a significant relationship between FOMO and consumptive behavior among Guidance and Counseling students at FKIP Nusa Cendana University as evidenced by the value of r-count > r-table 0, 5970 > 0,2404.